Constantinople dans quelques textes grecs de fiction aux XVIIIe et XIXe siècles - Henri Tonnet (Cahiers Balkaniques)
The present article is a presentation of the city of Istanbul as it appears in 19th century texts, in Greek novels. At the time Constantinople/Istanbul still felt like the natural capital of Hellenism for Greeks. The point that all those texts have in common, in the particular period, is that they underline the continuity between the Byzantine Empire and the Ottoman Empire. Even if at some points the Greek element of the population is over evaluated – there is rare if ever any mention of Turks in those texts – it is never idealized. The Greek neighbourhoods are described as being dirty and certain authors, like Constantine Ramfos, appear to be very sensible to the beauty of the ottoman architecture. These rare and non translated texts reveal to our eyes the city of Istanbul as a city that has now disappeared.